Components of Effective Supervision and Training for Paraeducators. (March 2023) - Bagawan, Atikah; Douglas, Sarah N.; Gerde, Hope K.
Special education teachers collaborate with numerous professionals, including paraeducators, who are tasked with supporting student learning in various school settings. In their role with paraeducators, teachers provide supervision, training, and coaching to enhance paraeducator skills to support students with disabilities in the classroom. This column provides an approach to paraeducator supervision, training, and coaching guided by the adult learning principles outlined in Kolb's experiential learning model. In addition, sample fidelity checklists and observation forms are included for use during training and coaching sessions to enrich the paraeducator's learning experience. Armed with these resources, teachers can cocreate meaningful and authentic learning opportunities in which paraeducators identify individual goals and reflect on their teaching with guidance from the teacher. As a result, teachers and paraeducators work together to provide quality instruction.